Literary pseudonyms and their formation - Avezova , Dilovar (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
This scientific article analyzes the origin of literary pseudonyms, the factors influencing their formation, and their role in fiction. It also explores the traditions of choosing pseudonyms, their spiritual and aesthetic content, and their significance in expressing the creative personality of the author.